1976
DOI: 10.1152/jappl.1976.41.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volume history on successive partial expiratory flow-volume maneuvers

Abstract: In normal subjects, the second of two successive partial expiratory flow-volume (PEFV 2) curves often had higher isovolume maximal expiratory flow rates (Vmax) than the first (PEFV 1) (mean increase 30.2 +/- 13%). The higher Vmax on PEFV 2 was present only when there was a greater lung elastic recoil pressure (Pst(L)). In eight subjects the Pst(L) derived from sequential partial quasi-static pressure-volume curves, from interruption of the flow-volume maneuvers and at the start of the PEFV curves showed that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…In this connection, it should be noted that similar considerations pertain to comparison of tidal V-V curves with those obtained during partial forced expirations. Indeed, WELLMAN et al [35] have shown that in normal subjects the maximal flows obtained during a forced expiratory manoeuvre started from FRC depend on the previous volume history, similar to the FVC manoeuvres. By contrast, with the NEP method, the previous volume history is by definition fixed (figs 2 and 3).…”
Section: Discussionmentioning
confidence: 80%
“…In this connection, it should be noted that similar considerations pertain to comparison of tidal V-V curves with those obtained during partial forced expirations. Indeed, WELLMAN et al [35] have shown that in normal subjects the maximal flows obtained during a forced expiratory manoeuvre started from FRC depend on the previous volume history, similar to the FVC manoeuvres. By contrast, with the NEP method, the previous volume history is by definition fixed (figs 2 and 3).…”
Section: Discussionmentioning
confidence: 80%
“…Wellman et al showed that the SF peaks obtained in partial maximal expiratory-flow curves decreased in successive maneuvers, thus implicating the involvement of the viscoelastic properties of the airway wall in the genesis of the SF peaks [13]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is not a single maximal flow-volume curve but rather a family of different curves, which depend on the time course of the inspiration preceding the FVC manoeuvre [35][36][37]. 4) Respiratory mechanics and time constant inequalities are different during the tidal and maximal expiratory efforts, again making comparisons of the two flow-volume curves problematic [38][39][40]. 5) Exercise may result in bronchodilation or bronchoconstriction and other changes of lung mechanics, which may also affect correct comparisons of the two flow-volume curves [41].…”
Section: Conventional (Hyatt's) Methodsmentioning
confidence: 99%